Comparison of droplet digital PCR and conventional quantitative PCR for measuring EGFR gene mutation - ZHANG, BO (Exp Ther Med, 2015)
Early detection of epidermal growth factor receptor (EGFR) mutation, particularly EGFR T790M mutation, is of clinical significance. The aim of the present study was to compare the performances of amplification refractory mutation system-based quantitative polymerase chain reaction (ARMS-qPCR) and droplet digital polymerase chain reaction (ddPCR) approaches in the detection of EGFR mutation and explore the feasibility of using ddPCR in the detection of samples with low mutation rates. EGFR gene mutations in plasmid samples with different T790M mutation rates (0.1–5%) and 10 clinical samples were detected using the ARMS-qPCR and ddPCR approaches. The results demonstrated that the ARMS-qPCR method stably detected the plasmid samples (6,000 copies) with 5 and 1% mutation rates, while the ddPCR approach reliably detected those with 5% (398 copies), 1% (57 copies), 0.5% (24 copies) and 0.1% (average 6 copies) mutation rates. For the 10 clinical samples, the results for nine samples by the ARMS-qPCR and ddPCR methods were consistent; however, the sample N006, indicated to be EGFR wild-type by ARMS-qPCR, was revealed to have a clear EGFR T790M mutation with seven copies of mutant alleles in a background of 6,000 wild-type copies using ddPCR technology. This study demonstrates the feasibility of applying the ddPCR system to detect EGFR mutation and identified the advantage of ddPCR in the detection of samples with a low EGFR mutation abundance, particularly the secondary EGFR T790M resistance mutation, which enables early diagnosis before acquired resistance to tyrosine kinase inhibitors becomes clinically detectable.